SOCIALIZATION OF MENTAL HEALTH FOR PREGNANT WOMEN THROUGH “HOLDING BY HUSBANDS” IN SUPPORTING A PROSPEROUS PREGNANCY PERIOD - Probowati, Rovica; Buyu Prakoso, Adi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Mental health is an important component of overall well-being, especially for pregnant women and has an impact on the fetus. WHO reports that 1 in 5 women will experience mental health problems during pregnancy or one year after giving birth. The impact of mental health problems on mothers will have physical and psychological impacts on both the mother and her baby, such as maternal depression, postpartum depression, and can have an impact on the birth of low birth weight (LBW) babies. Objective: This community service is to socialize the importance of mental health for pregnant women by prioritizing the role of